Akzente in Bibelhandschriften aus der Kongregation von Windesheim: Der Libellus de accentuatione terminorum Bibliae, mit einer Edition des Begleitschreibens des Generalpriors - Overgaauw, Eef 1957- (2023)
Among the canons in monasteries of the Congregation of Windesheim, a fierce debate arose in the third quarter of the 15th century about the correct pronunciation of the names of biblical places and persons, mainly of Greek or Hebrew origin. In order to mitigate this debate and to ensure unity within the Congregation, the General chapter installed a commission who should decide in all possible cases about the correct pronunciation. This unifying mandate of the commission was summarized in the Libellus de accentuatione terminorum Bibliae. This Libellus mainly consists of shorter and longer lists of words in each book of the Bible with the correct accent or accents. Together with a severe admonition of the Prior general, the Libellus was to be distributed to all monasteries members of the Congregation of Windesheim. According to the admonition, the debate about the correct pronunciation of foreign words should be ended immediately to ensure uniformity in the relevant manuscripts of the Bible and concord among the debating patres and fratres. All available Bibles should be corrected according to the lists of the Libellus. A first survey of Bible manuscripts from Windesheim monasteries shows, that the Prior general’s admonition was duly implemented. Existing accents were corrected in most of the Bibles, missing accents were systematically added.